Réponses

2013-12-31T03:11:11+01:00
A = (2x - 3)² + (2x + 5)²
A = (2x)² - 12x + 3² + (2x)² + 20x + 5²
A = 4x² - 12x + 9 + 4x² + 20x + 25
A = 8x² + 8x + 34.

B = (5x - 3)(5x + 3) - 4(x + 2)(x + 3)
B = 25x² + 15x -15x - 9 - 4(x² + 3x + 2x + 6)
B = 25x² + 15x -15x - 9 - 4(x² + 5x + 6)
B = 25x² + 15x -15x - 9 - 4x² - 20x - 24
B = 21x² - 20x - 33.

C = (x + 2)² - (x - 5)² + (x - 4)(x + 4)
C = x² + 4x + 2² - (x² - 10x + 5²) + x² + 4x - 4x - 16
C = x² + 4x + 4 - (x² - 10x + 25) + x² + 4x - 4x - 16
C = x² + 4x + 4 - x² + 10x - 25 + x² + 4x - 4x - 16
C = x² + 14x - 37.